2017
DOI: 10.1007/s13197-017-2898-8
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional properties of bioactive peptide fractions from protein isolates of moringa seed (Moringa oleifera)

Abstract: (Moringaceae) is a specie of significant importance because of its multiple nutraceutical properties, that has led to increase in its consumption. The seeds contain a high percentage of protein (37.48%). However, little is known about the bioactive properties of these proteins and peptides, especially those generated by enzymatic hydrolysis. The objective of this study was to evaluate the biofunctional properties of total hydrolysates (TH) and peptide fractions from protein isolates of moringa seeds. Isoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 34 publications
1
17
0
1
Order By: Relevance
“…The enzymes trypsin, chymotrypsin, and pepsin-trypsin are utilised for the first two and a half and five hours, respectively. The use of the pepsin-trypsin digested fraction for hydrolysis intervals of 5 h and 5 h, respectively, for alpha-amylase inhibition was validated, with IC50 values of 0.195 and 0.123 g/ml, respectively, confirming the findings of the previous research [ 59 ]. The IC50 for alcalase hydrolysate was modified and determined to be 0.149 mg/ml for protein hydrolysate of watermelon seeds received with the useful beneficial resource of enzymes together with pepsin, trypsin, and alcalase [ 60 ].…”
Section: Introductionsupporting
confidence: 85%
“…The enzymes trypsin, chymotrypsin, and pepsin-trypsin are utilised for the first two and a half and five hours, respectively. The use of the pepsin-trypsin digested fraction for hydrolysis intervals of 5 h and 5 h, respectively, for alpha-amylase inhibition was validated, with IC50 values of 0.195 and 0.123 g/ml, respectively, confirming the findings of the previous research [ 59 ]. The IC50 for alcalase hydrolysate was modified and determined to be 0.149 mg/ml for protein hydrolysate of watermelon seeds received with the useful beneficial resource of enzymes together with pepsin, trypsin, and alcalase [ 60 ].…”
Section: Introductionsupporting
confidence: 85%
“…The quantity of determined crude proteins in dry leaves of M. oleifera from South Africa was 30.3% [27]. However, maximum protein content (37.5 g/100 g of DW) was recently reported for M. oleifera seeds cultivated in Mexico [39]. It has been suggested that the protein quantity depends not only on the cultivars and species but also on environmental factors.…”
Section: Discussionmentioning
confidence: 98%
“…Its therapeutic value as a cardioprotective, hepatoprotective, neuroprotective, anti-asthmatic, anti-tumor, antimicrobial, hypolipidemic, modulator of intestinal microbiota and antidiabetic agent derives from its phytochemical constituents such as alkaloids and polyphenols [ 4 , 5 , 6 ]. In addition, bioactivity has been proved for peptide fractions (i.e., inhibition of alfa-amylase and angiotensin converting enzyme-1 activities) [ 7 ], isolated polysaccharide fractions [ 8 , 9 ] or the isothiocyanate derivatives of characteristic glucosinolates [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%